Why interventions in the seed systems of roots, tubers and bananas crops do not reach their full potential - Almekinders, Conny J.M.; Walsh, S.; Jacobsen, K.; Andrade-Piedra, J.L.; McEwan, M.; Haan, Stef de; Kumar, L.; Staver, Charles (Springer, 2019)
Seed systems for roots, tuber, and banana (RTB) crops receive relatively little attention from development-oriented research and commercial seed sector actors, despite their importance for food security, nutrition and rural livelihoods. We review RTB seed systems—with particular reference to potato, sweetpotato, cassava, yam and banana —to reflect on current seed system development approaches and the unique nature of these systems. We refer to our own experiences, literature and 13 case studies of RTB seed system interventions to identify gaps in our knowledge on farmer practices in sourcing and multiplying seed, and processes affecting seed quality. Currently, most approaches to developing RTB seed systems favour decentralised multiplication models to make quality seed available to smallholder farmers. Nevertheless, arguments and experiences show that in many situations, the economic sustainability of these models cannot be guaranteed, among others because the effective demand of farmers for seed from vegetatively propagated crops is unclear. Despite the understudied nature of farmers’ agronomic and social practices in relation to seed production and sourcing in RTB crops, there is sufficient evidence to show that local RTB seed systems are adaptive and dynamic. Our analysis suggests the paramount importance of understanding farmers’ effective demand for seed and how this affects the sustainable supply of quality seed from specialized producer-entrepreneurs, regardless of the seed system paradigm. From the case studies we learnt that few interventions are designed with a rigorous understanding of these issues; in particular, what types of interventions work for which actors, where, and why, although this is a necessary condition for prioritizing investments to increase the use of improved seed by smallholder farmers.